Physiological Stimulation of the Synthesis of Preelastic Fibers in the Dermis of a Patient with Fibrosis - Jose Maria Pereira de Godoy; Lívia Maria Pereira de Godoy; Maria de Fatima Guerreiro Godoy; Dalisio de Santi Neto (Case Reports in Medicine)
Objective. The aim of the present study was to report the physiological stimulation of the synthesis of preelastic fibers in the dermis of a patient with fibrosis. Design. A clinical study was conducted involving the analysis of histological changes in preelastic fibers following treatment for stage II primary lymphedema for the clinical reversal of lymphedema and fibrosis. Setting. University Hospital of the São Jose do Rio Preto of School of Medicine in 2020. Participant was a 67-year-old male patient with late-onset primary lymphedema diagnosed 12 years earlier. Intervention is the lymphatic stimulation using the Godoy method adapted to the treatment of fibrosis. Main outcomes and measures are biopsies before and after treatment. Ten randomly selected histological fields were evaluated using the multipoint morphometric method. The values with this method are relative and expressed as percentages. Statistical analysis was performed with the t-test, considering a 95% significance level. Results. A visible, significant difference in the percentage of preelastic fibers was found between the preintervention and postintervention slides, which were confirmed by the microscopic evaluation and quantification (4.95 ± 0.64% and 14.70 ± 1.06%, respectively). Conclusion. The physiological stimulation of the lymphatic system using a specific method resulted in the clinical reduction of fibrosis, the return of the elasticity of the skin, and the stimulation of the synthesis of preelastic fibers.